Desain Ulang Pompa Electrical Submersible Pump (ESP) Untuk Mengoptimalkan Produksi Pada Sumur “FAM-2301” Lapangan Gefima - Feliksta Agatha Mambela; Deny Fatrianto Edyzoh Eko Widodo; Nijusiho Manik; Aprilino Alfa Kurmasela; Roﬁma Sera Aﬁfah; Reyhandri Anugrah; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
The "FAM-2301" well in the "Gefima" field is a well that has just started producing using an artificial lift type Electrical Submersible Pump. So it is necessary to increase the flow rate (q) using the one-phase IPR method. In this well, an Artificial Lift Design was carried out using the Electrical Submersible Pump (ESP) method to increase the flow rate using the one-phase IPR method. In this final project research, the aim is to obtain the results of the redesign of the installation of new pumps and motors. From the design results of the "FAM-2301" well, it shows that the optimum flow rate obtained is 570 BFPD, while it is also obtained that the type of pump used in the "FAM-2301" well is REDA RC 1000 - 60Hz which has a pump efficiency of 58% while the motor used is the 456 series (37.5 HP, 578 Volts, and 42.5 A) so that it can be ensured that the pump can work properly.